Dialogic skills in RE: recontextualising the dialogue school - Luby, Antony (Journal of Religious Education, 2019)
As the Catholic Church encounters secularism and pluralism, one of her main responses has been dialogue. Some of the prime manifestations have been the political initiative of the Courtyard of the Gentiles and the plea from the Congregation for Catholic Education for a grammar of dialogue as envisaged in the recent document Educating for fraternal humanism. Arguably, the most developed response is to be found in the Australian Dialogue School model mooted by theologians from the Catholic University of Leuven, Belgium. This paper outlines some of the findings from a recent PhD thesis that examines the dialogic skills of building consensus through cumulative talk and constructive criticism through exploratory talk. It is advocated that teachers use the medium of paired conversations between students in the secondary stage of schooling in order to develop such dialogic skills.